2014
DOI: 10.1177/0042098014534903
|View full text |Cite
|
Sign up to set email alerts
|

Has the Community Reinvestment Act increased loan availability among small businesses operating in minority neighbourhoods?

Abstract: The 1977 Community Reinvestment Act (CRA) established a bold agenda requiring financial institutions in the USA to serve the credit needs of low-and moderate-income areas, including traditionally excluded minority residential areas. Initially opposed by both bankers and the federal regulatory authorities responsible for enforcement, the CRA has been contentious for decades. This study explores CRA impacts by investigating whether small businesses located in minority neighbourhoods have the same degree of bank-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…Alternative specifications of Table 3's regression model generate results consistent with the findings discussed here; see Bates and Robb (2015). A "business," by definition, was created by one or more people and includes purchasing an existing business or a franchise.…”
Section: Authors' Notesupporting
confidence: 72%
See 3 more Smart Citations
“…Alternative specifications of Table 3's regression model generate results consistent with the findings discussed here; see Bates and Robb (2015). A "business," by definition, was created by one or more people and includes purchasing an existing business or a franchise.…”
Section: Authors' Notesupporting
confidence: 72%
“…Logistic regression analysis revealed that MBEs located in minority neighborhoods were actually more likely to have their applications approved by banks than minority businesses located elsewhere in urban America (Bates & Robb, 2015). Logistic regression analysis revealed that MBEs located in minority neighborhoods were actually more likely to have their applications approved by banks than minority businesses located elsewhere in urban America (Bates & Robb, 2015).…”
Section: Background: Discriminatory Practices Limiting Access To Bankmentioning
confidence: 96%
See 2 more Smart Citations
“…Statistical analyses find that race remains a negative predictor of loan acceptance and loan quality, even after controlling for salient economic characteristics (Asiedu et al, 2012 ; Blanchard et al, 2008 ; Blanchflower et al, 2003 ). Other work has confirmed that these disparities are not merely due to location-based “redlining” but are primarily a function of the entrepreneur’s own race (Bates & Robb, 2015 , 2016 ). This discrimination can be clearly observed in “mystery shopper” studies that document severe disparities in the way bank employees treat equally qualified Black and white entrepreneurs asking for identical loans (Bone et al, 2014 , 2017 ; Lubin, 2011 ; Turner et al, 2002 ).…”
Section: Introductionmentioning
confidence: 97%